What Makes Successful Ageing «Successful»? : Reflections from a Bioethical Perspective (Revista Iberoamericana de Bioética, 2020)
Ageing has aroused great interest in recent decades, stimulating the emergence of many explanatory and descriptive models, one of the most prominent of these being “Successful Ageing”. However, interest in old age seems to have started from quantitative and economic aspects, characterizing it as a social problem. This fact, coupled with the frequent stereotypes and social prejudices about the elderly, has turned old age into a factor of marginality. Therefore, this article aims to reflect on some possible factors, psychological and psychosocial, involved in a supposed ageing considered successful, but from a bioethical perspective, that ensures a focus of interest on the autonomy, dignity and freedom of people.
Keywords: successful ageing; psychological and psychosocial factors; autonomy